An evaluation of a multi-site fetal alcohol spectrum disorder models of care project - Panton, Kirsten R.; Fitzpatrick, James P.; Pestell, Carmela F. (Frontiers in Public Health, 2023)
Fetal alcohol spectrum disorder (FASD) continues to be underdiagnosed in Australia, partly due to the lack of trained clinicians and diagnostic services. This project aimed to help increase FASD knowledge and diagnostic capacity across Australia. Six sites across Australia formed part of a national consortium, delivering training clinics, diagnostic clinics and community education sessions. The number of FASD diagnoses significantly increased across the project. Additionally, the number of community education sessions steadily increased across the project, with largely positive feedback. Participants attending the training clinics demonstrated increased knowledge of and confidence in FASD diagnosis. This evaluation showcases the benefits of a coordinated approach to prevention, assessment, diagnosis and training in FASD.